Factors affecting antimicrobial stewardship program implementation in select public health centers in Pasay City a qualitative study - Arbas, Oellyssa B.; Marturillas, Shaneika Nicole G.; Tronco, James Louie D.; Yuag, Gianyhle Shynne G. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Antimicrobial Stewardship Programs (ASPs) are essential for preserving antibiotic effectiveness. However, their implementation in primary health care (PHC) settings in the Philippines is relatively new and remains unclear. This study aimed to assess the current implementation status of ASPs in selected public health centers in Pasay City by evaluating the presence of core elements outlined in the Manual of Procedures (MOP), and describing both enabling and limiting factors faced by health center staff. A descriptive qualitative research design was employed with a quota sampling of at least nine (9) key interview informants comprising eight (8) respondents from select health centers—two (2) from each profession expected to be part of the AMS Team—and one (1) point person responsible for ASP implementation from the City Health Office (CHO). Semi-structured interviews were conducted in select health centers in Pasay City. The implementation of the six (6) core ASP elements presented an informal and under-resourced structure at the PHC level, particularly lacking dedicated pharmacists and consistent policy dissemination. Results also showed that while basic clinical practices and reporting systems were in place, significant gaps remained in staff training, data management, and performance feedback, limiting the effectiveness and sustainability of antimicrobial stewardship at the primary care level. Enabling factors found include strong leadership support from the CHO and local government, the commitment of PHC staff, free access to essential antimicrobials, consistent patient education, and external motivation from accreditation requirements. However, major limiting factors such as manpower shortages—especially the absence of pharmacists—manual data systems, lack of formal ASP training, and patient-related challenges like non-adherence and low health literacy hinder consistent and effective stewardship practices.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Public health -- Drug policy -- Evaluation -- Philippines; Antimicrobial stewardship -- Implementation -- Public health facilities -- Philippines -- Pasay City; AMS; ASP; enabling factors; limiting factors; primary healthcare setting